FlowEmu: An Open-Source Flow-Based Network Emulator - Stolpmann, Daniel; Timm-Giel, Andreas (Electronic Communications of the EASST, 2021)
When analyzing the impact of a communication system on the Quality of Experience (QoE) of an interactive application, simulation and mathematical modeling typically require reimplementation or modeling of the application under test and only provide insights in terms of selected Key Performance Indicators (KPIs), which raises the need for network emulation. In this demo, we present FlowEmu, an open-source flow-based network emulator that allows the user to manipulate the underlying model and analyze various statistics in real-time via an easy-to-use Graphical User Interface (GUI), by using interactive game streaming as an example application.